Sang de belette et cervelle de corbeau : la médicalisation de la folie au Québec, 1600-1850 - Cellard, André (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1993)
Like most areas of health that interested medicine in the 19th century, it was almost without opposition that insanity was to become a new medical specialty during the past century. The aim of this article is to shed some light on the dynamics that have allowed doctors since the I7tl% and 18th century to share their point of view with the general public for whom the existential causes of madness seem to have been taken for granted.